2012
DOI: 10.18632/aging.100436
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of MEF2C signaling and loss of sarcomeric and mitochondrial integrity in cancer-induced skeletal muscle wasting

Abstract: Cancer cachexia is a highly debilitating paraneoplastic disease observed in more than 50% of patients with advanced cancers and directly contributes to 20% of cancer deaths. Loss of skeletal muscle is a defining characteristic of patients with cancer cachexia and is associated with poor survival. The present study reveals the involvement of a myogenic transcription factor Myocyte Enhancer Factor (MEF) 2C in cancer-induced skeletal muscle wasting. Increased skeletal muscle mRNA expression of Suppressor of Cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 34 publications
(48 reference statements)
10
67
0
Order By: Relevance
“…However, at the time point that we analyzed we did not observe any change in the expression of TGFβ or any of the family members that we considered, at least in our experimental model. Ultimately, based on our findings, the occurrence of muscle weakness following chemotherapy administration may well result from a combined effect associated with the reduction of mitochondrial content and the loss of sarcoplasmic/structural proteins, as also suggested by detecting thinner Z-lines and I-bands [51, 53]. …”
Section: Discussionmentioning
confidence: 89%
“…However, at the time point that we analyzed we did not observe any change in the expression of TGFβ or any of the family members that we considered, at least in our experimental model. Ultimately, based on our findings, the occurrence of muscle weakness following chemotherapy administration may well result from a combined effect associated with the reduction of mitochondrial content and the loss of sarcoplasmic/structural proteins, as also suggested by detecting thinner Z-lines and I-bands [51, 53]. …”
Section: Discussionmentioning
confidence: 89%
“…Distorted mitochondria are present in muscle during cancer cachexia [13] and this is associated with loss of skeletal muscle structural integrity. Different research groups have shown that, in spite of the fact that the UCP2 gene is overexpressed in skeletal muscle from cachectic rats [14,15] and that muscle oxidative capacity -complex IV activity -is decreased, no alteration in either ATP synthesis or uncoupling are observed.…”
Section: Oxidative Damage and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Myocyte Enhancer Factor (MEF) 2C, a myogenic transcription factor, is significantly downregulated in skeletal muscle from cachectic mice. Since MEF2C targets myozenin and myoglobin, it seems to be associated with deregulated oxygen transport capacity and ATP regeneration [13].…”
Section: Oxidative Damage and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Several of the genes shared across multiple over-represented pathways have been previously studied in models of muscle wasting and cachectic patients including FOS [50,60], FoxO1 [50,61,62], IL-6 receptor (IL6Ra) [63,64], MEF2C [65] and p21 (CDKN1A) [66,67]. Of note, both extensively characterized E3-ligases, MuRF-1 (TRIM63) and Atrogin-1 (Fbxo32), were among the 147 overlapping genes (Supplemental Table 1) though only MuRF-1 was part of an over-represented pathway ( Figure 5C).…”
Section: Importance Of Cytokine and Immune Signaling Pathways In Thementioning
confidence: 99%